(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: This study explores the effectiveness of using authentic materials to develop speaking skills among B1 level French language learners. The research was conducted over six weeks and involved an experimental group using authentic French-language media and a control group using textbook-based instruction. Through pre- and post-tests, classroom observation, and student feedback, the study measured fluency, vocabulary acquisition, pronunciation, and learner confidence. The results indicated that authentic materials had a significant positive impact on speaking performance, especially in terms of natural language usage and learner motivation. The findings suggest that authentic resources should be integrated into communicative French language teaching to enhance speaking skills at the B1 level.